Clinical correlates of severe thrombocytopenia from temozolomide in glioblastoma patients. Issue 10 (4th October 2018) - Arulananda, Surein; Lynam, James; Sem Liew, Mun; Wada, Morikatsu; Cher, Lawrence; Gan, Hui K.
Abstract: Background/Aim: This study was conducted retrospectively to evaluate rates of thrombocytopenia and their clinical impact during chemo‐radiotherapy for glioblastomas and to elucidate associated clinical factors. Methods: A total of 64 patients who received temozolomide chemotherapy at our institution was included; 35 patients received full‐dose chemo‐radiotherapy as per the STUPP protocol (Group A), and 9 patients received abbreviated radiotherapy with concurrent chemotherapy (Group B). Twenty patients received temozolomide alone with an intended 12 cycles of therapy for first relapse at least 6 months after completion of adjuvant chemotherapy (Group C). Results: In Group A, 27 of 35 (77%) patients completed the chemo‐radiotherapy phase; 14% had grade 3–4 thrombocytopenia leading to discontinuation. Of 27 patients, 16 (59%) completed adjuvant chemotherapy. There were no grade 3–4 thrombocytopenias, but 4% discontinued due to grade 2 thrombocytopenias. In Group B, four of nine (45%) patients completed the chemo‐radiotherapy phase; 11% had grade 3–4 thrombocytopenias and discontinued treatment. Three of four (75%) patients completed adjuvant chemotherapy. Of these, 75% had grade 3–4 thrombocytopenias, but none discontinued. Finally, in Group C, 8 of 20 (40%) patients completed, with 10% discontinuing due to thrombocytopenias and the rest due to disease progression. In exploratory analyses, being female increased the risk of myelosuppresion, and there was a trend noticed in patients having a higher body surface area. Conclusion: Our toxicity data were within range of the literature. We identified the group of patients that have increased thrombocytopenia risk. Larger pooled retrospective series and prospective studies are required.